Circulation and exchange in a broad Arctic fjord using glider-based observations. Issue 1 (1st January 2018) - Fraser, Neil J.; Skogseth, Ragnheid; Nilsen, Frank; Inall, Mark E.
ABSTRACT: In recent years, Svalbard fjords have experienced a substantial reduction in winter sea-ice extent. This has been linked to changes in wind stress patterns over Fram Strait and an increased transport of warm Atlantic Water into the fjords. In November 2014, we deployed two Slocum gliders to Isfjorden and measured the hydrographical properties and depth-averaged currents in the region. The campaign marked the first time gliders have been used inside an Arctic fjord. We observed geostrophically balanced flow patterns both in the mouth, where the heat flux into the fjord was calculated to be 0.13 TW, and in the interior of Isfjorden, where geostrophic flows were up to 20 cm s −1 . After a change in the prevailing wind direction on the West Spitsbergen Shelf, we found evidence for a wind-driven geostrophic control mechanism at the fjord mouth, impeding fjord–shelf exchange, and found that the geostrophic circulation inside the fjord had broken down. We conclude that the circulation patterns in Isfjorden are heavily influenced by rotational effects and by wind activity both locally and on the West Spitsbergen Shelf, and that geostrophically balanced exchange flows may deliver Atlantic Water to the fjord interior given the correct conditions at the fjord mouth. The combination of hydrography and high-resolution velocity data from throughout the Isfjorden region provided new insights into the circulation here, suggesting that this approach will be useful for studying high-latitude fjords in the future.